The Influence Of Role, Supervision, Controlling And Motivation Health Personnel On Stunting Coverage In Health Center South Nias District - Putri Satriani Dachi; Ermi Girsang; Sri Lestari Ramadhani Nasution (Sean Institute, 2024)
According to the Indonesian Ministry of Health, there are several factors that cause stunting in children, including mothers not having access to healthy and nutritious food such as high protein foods, which causes their children to also lack nutrition. The incidence of stunting has decreased between 2020 and 2021, the prevalence of stunting globally has decreased from 32.6 percent to 22.2 percent, the number of children affected by stunting has decreased from 198 million to 151 million. The aim of this research is to determine whether there is an influence between the role, supervision, control and motivation of health workers on stunting coverage in the South Nias District Health Center. The type of research used is quantitative analytics. The research design is a cross-sectional study. The sampling technique in this research is the total population, that is, the entire population is used as the research sample, so the total sample in the research is 360 employees. The results of the research explain that there is an influence between the role, supervision, control and motivation of health workers on stunting coverage in the South Nias District Health Center. It is hoped that this research can have a positive impact on the coverage of stunting in the South Nias Regency Health Center.